Enantioselective Synthesis of Pyrroloindolines via Non-Covalent Stabilization of Indole Radical Cations and Applications to the Synthesis of Alkaloid Natural Products - Gentry, Emily C. (J Am Chem Soc, 2018)
While interest in the synthetic chemistry of radical cations continues to grow, controlling enantioselectivity in the reactions of these intermediates remains a challenge. Based on recent insights into the oxidation of tryptophan in enzymatic systems, we report a photocatalytic method for the generation of indole radical cations as hydrogen-bonded adducts with chiral phosphate anions. These non-covalent open-shell complexes can be intercepted by the stable nitroxyl radical TEMPO• to form alkoxyamine-substituted pyrroloindolines with high levels of enantioselectivity. Further elaboration of these optically-enriched adducts can be achieved via a catalytic single-electron oxidation/mesolytic cleavage sequence to furnish transient carbocation intermediates that may be intercepted by a wide range of nucleophiles. Taken together, this two-step sequence provides a simple catalytic method to access a wide range of substituted pyrroloindolines in enantioenriched form via a standard experimental protocol from a common synthetic intermediate. The design, development, mechanistic study, and scope of this process are presented, as are applications of this method to the synthesis of several dimeric pyrroloindoline natural products.